The Effect of the Substrate Temperature and the Height of the Mini-Channel on the Evaporation of Liquid Droplet Blown by the Gas Flow; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Isachenko E. Ekaterina (2016, 2016)
Title screen